Application Of Image Media In Science Learning To Improve Learning Outcomes Of Grade IV Elementary School Students - Awaliyah, Siti Soliha; Kalifah, Diah Rizki Nur (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2025)
The purpose of the study was to determine the application of image media in science learning in improving the learning outcomes of fourth grade elementary school students. The type of research is classroom action research (CAR). The research design adopts the Kemmis and Taggart model consisting of two cycles, each cycle includes planning, implementation, observation, and reflection. The subjects of the study were 35 fourth grade elementary school students , consisting of 20 males and 15 females . Data collection through observation, interviews, and documentation. Data analysis in this study used qualitative data analysis, namely with statistical models such as tables and diagrams from the results of observations and values of each cycle and using quantitative data analysis by comparing data obtained from the implementation of cycle I and cycle II activities. The results of the study showed an increase in learning outcomes after the application of image media in the subject of science as evidenced by the average value of cycle I obtained 85 with a percentage of 51%, there were 18 students who completed. While in cycle II obtained an average value of 90 with a percentage of 80% and there were 28 students who completed. So it can be concluded that from cycle I and cycle II there was an increase in student learning outcomes after the application of image media.